Photoswitchable glycoligands targeting Pseudomonas aeruginosa LecA - Fan, Yu; El Rhaz, Ahmed; Maisonneuve, Stéphane; Gillon, Emilie; Fatthalla, Maha; Le Bideau, Franck; Laurent, Guillaume; Messaoudi, Samir; Imberty, Anne; Xie, Juan (Beilstein Journal of Organic Chemistry, 2024)
Biofilm formation is one of main causes of bacterial antimicrobial resistance infections. It is known that the soluble lectins LecA and LecB, produced by Pseudomonas aeruginosa, play a key role in biofilm formation and lung infection. Bacterial lectins are therefore attractive targets for the development of new antibiotic-sparing anti-infective drugs. Building synthetic glycoconjugates for the inhibition and modulation of bacterial lectins have shown promising results. Light-sensitive lectin ligands could allow the modulation of lectins activity with precise spatiotemporal control. Despite the potential of photoswitchable tools, few photochromic lectin ligands have been developed. We have designed and synthesized several O- and S-galactosyl azobenzenes as photoswitchable ligands of LecA and evaluated their binding affinity with isothermal titration calorimetry. We show that the synthesized monovalent glycoligands possess excellent photophysical properties and strong affinity for targeted LecA with Kd values in the micromolar range. Analysis of the thermodynamic contribution indicates that the Z-azobenzene isomers have a systematically stronger favorable enthalpy contribution than the corresponding E-isomers, but due to stronger unfavorable entropy, they are in general of lower affinity. The validation of this proof-of-concept and the dissection of thermodynamics of binding will help for the further development of lectin ligands that can be controlled by light.
Keywords: carbohydrates; glycosyl azobenzenes; lectin A; photoswitchable ligands